Compliance Profile of Pulmonary Tuberculosis Patient Treatment Stage in Consuming Anti Tuberculosis Drugs (ATD) at Lubuk Buaya Health Center Padang - Rinita Amelia; Nilas Warlem; Dessy Abdullah; Satria Andhika (Institute of Computer Science (IOCS), 2022)
A well-prepared abstract enables the reader to identify the basic Tuberculosis (TB) is a disease caused by the microorganism Mycobacterium tuberculosis. According to the World Health Organization (WHO), the prevalence global of TB in 2018 was around 10 million people infected and caused 1.5 million deaths. Eradication TB, it is necessary to be aware of the patient himself because adherence to taking ATD is a key factor in the success of the treatment. The purpose of this study was to determine the compliance profile of pulmonary TB patients in consuming Anti-TB Drugs (ATD) at Lubuk Buaya Health Center, Padang City in 2019-2020. Type of research is descriptive research with cross-sectional study method and total sampling. Univariate data analysis is presented by distribution freququency. Data processing using the computerized SPSS program. The results of research showed 117 patients who met the inclusion and exclusion criteria. The most of patient is 26-45 years old, namely 51 people (43,6%). The Most of gender is male, namely 65 people (55,6%). The most job of patient is entreprenur, namely 35 people (29,9%). The most of education category is a middle category, namely 69 people (59,0%). The most of treatment stage is continuation stage, namely 99 people (84,6%). The most of ATD category is the first category , namely 100 people (85,5%), and the most patient to complied to taking ATD, namely 99 people (84,6%). This research was concluded that age 26-45 years old, gender is male, job is entreprenur, education is a middle category, stage of treatment is continuation category, the first category of ATD, patient to complied to taking ATD is the dominant profile pulmunary TB patient at Lubuk Buaya health center in 2019-2020.